Learning automata-based techniques for maximizing lifetime in solving target coverage problems in directional sensor networks [electronic resource] - Hosein Mohamadi, 1983- (2013)
Thesis (Ph.D (Sains Komputer)) - Universiti Teknologi Malaysia, 2013